Chronic Vascular Effects of Oat Phenolic Acids and Avenanthramides in Pre- or Stage 1 Hypertensive Adults. (29th May 2020) - Spencer, Jeremy; Soycan, Gulten; Corona, Giulia; Johnson, Jodee; Chu, YiFang; Shewry, Peter; Lovegrove, Alison
Abstract: Objectives: Wholegrain consumption is linked to a lower risk of cardiovascular disease. Evidence have established that the consumption of wholegrain oats lowers blood cholesterol, via a mechanism partly mediated by β-glucan. However, oats contain an array of phenolics, including ferulic acid and avenanthramides, which may also contribute to the cardiovascular health benefits. We investigated whether daily consumption of oat phenolics leads to improvement of markers of CVDrisks in adults. Methods: In a 3 arm crossover double-blind, placebo-controlled trial, 28 volunteers consumed either: 1) oatmeal/oatcake intervention (68.1 mg of phenolics); 2) oatbran concentrate + rice porridge/wheat cracker (38.9 mg of phenolics) or 3) rice porridge/wheat cracker (13.8 mg of phenolic acids) for 4 weeks. All treatments were matched in macro nutrients, energy (500 kcal) and total soluble fiber (4.8 g). The primary endpoint was flow mediated dilatation (FMD) and other cardiovascular endpoints were laser doppler imaging, 24 h blood pressure and LDL/HDL cholesterol. Results: Consumption of high phenolic oats led to a significant improvement in 24-hour SBP (−1.16 mm Hg), night time SBP (−5.1 mm Hg) and night time DBP (−2.3 mm Hg) ( P  < 0.05, P  < 0.01 and P  < 0.05, respectively). Our data indicate a non-significant increase by 1.09% ± 0.41% in FMD following high phenolic oat intake. Small increases in microvascular function and small decreases in total and LDL cholesterol after the consumption of moderate and high phenolic oats did not achieve significance. Conclusions: The findings of this study provide evidence that phenolic components in oats may in part, underpin their beneficial actions in cardiovascular protection. Funding Sources: Biological and Biotechnological Sciences Research Council (BBSRC).